The Influence of Leadership, Non-Physical Work Environment and Job Satisfaction on Employee Turnover Intention at the “SiCepat Ekspres” Expedition, Ponorogo Branch - Quliyawan, Ariyandi; Hartono, Sri; Wijianto, Wijianto (Nomico, 2025)
This study aims to determine the effect of leadership, nonficical workmanship and work statistics for turnover intention of employees in the Ponorogo Branch "SiCepat Ekspres" Expedition. Keywords: content; formatting; article.The sample used is as many employees as 41 people in Expdisi "SiCepat Ekspres" Ponorogo Branch.The method used in this study is multiple linear regression with the help of SPSS. The results of the study indicate that: (1) Leadership has a partial effect on employee turnover intention at Expedition "SiCepat Ekspres" Ponorogo Branch. (2) The nonficical woekmanship has a partial effect on employee turnover intention at Expedition "SiCepat Ekspres" Ponorogo Branch. (3) the job statisfaction has a partial effect on employee turnover intention at the Ponorogo Branch "SiCepat Ekspres" Expedition.